2008
DOI: 10.1098/rspb.2008.0990
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone responses to competition in men are related to facial masculinity

Abstract: Relationships between androgens and the size of sexually dimorphic male traits have been demonstrated in several non-human species. It is often assumed that a similar relationship exists for human male faces, but clear evidence of an association between circulating testosterone levels and the size of masculine facial traits in adulthood is absent. Here we demonstrate that, after experimentally determined success in a competitive task, men with more a masculine facial structure show higher levels of circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 57 publications
3
148
4
1
Order By: Relevance
“…Like others, we find that sex differences in face structure explain only 11% of perceived masculinity (6-11% in Koehler et al, 2004;Komori et al, 2011;Pound et al, 2009). Since morphological masculinity predicted gender in our sample correctly for 92.5% of faces, we suggest that the weak relationship between morphological and perceived masculinity cannot be explained by an inadequate structural estimation of sexual dimorphism.…”
Section: Discussionsupporting
confidence: 77%
“…Like others, we find that sex differences in face structure explain only 11% of perceived masculinity (6-11% in Koehler et al, 2004;Komori et al, 2011;Pound et al, 2009). Since morphological masculinity predicted gender in our sample correctly for 92.5% of faces, we suggest that the weak relationship between morphological and perceived masculinity cannot be explained by an inadequate structural estimation of sexual dimorphism.…”
Section: Discussionsupporting
confidence: 77%
“…These measures included others' ratings of facial dominance and of facial attractiveness; both of these variables positively predict ability to compete for resources in modern organisations (Fruhen, Watkins, & Jones, 2015), and the former is a positive predictor of male strength (Toscano, Schubert, & Sell, 2014). Facial variables also included objectively-measured facial shape masculinity (Penton-Voak et al, 2001), which, like muscularity, is believed to increase with developmental testosterone exposure and is correlated with circulating testosterone levels in adult males exposed to competitive stimuli (Pound, Penton-Voak, & Surridge, 2009). Moreover, we included facial width-to-height ratio (fWHR), a variable which has recently been shown to be associated with a range of related behavioural traits in males (for a review see Hodges-Simeon, Hanson Sobraske, Samore, Gurven, & Gaulin, 2016).…”
Section: The Current Studymentioning
confidence: 99%
“…There is some evidence that facial masculinity is associated with levels of circulating testosterone in men (Pound et al, 2009). However, some studies have found that women prefer more feminine male faces (Perrett et al, 1998) or found no preference for masculinity (Rhodes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%